A comparative study on the accessibility of e-government websites of Indonesia and the Philippines - Villaverde, Meily Dewi
As technology continues to advance, government agencies are trying their best to implement information technology; this has introduced the term e-government. E-government’s purpose serves its community but it is questionable whether accessibility was taken into consideration, especially for people with disabilities. Using Equally.ai and WAVE Web Accessibility Evaluation Tool, this study explores the current state of e-government websites in Indonesia and the Philippines, two culturally similar countries, and its adherence to the Web Content Accessibility Guidelines (WCAG) 2.1. The results showed that the 11 websites tested were able to fulfill the first three principles of the WCAG 2.1, Perceivable, Operable and Understandable, but failed to fulfill the Robust principle. Furthermore, news articles were collected to help contextualize the current situation. The results showed that accessibility in e-governance was not its main focus for both countries, thus making it hard for users, especially those with disabilities, to forage for information on the website.